Chronic Angiotensin II (AngII) – Induced Hypertension is Attenuated by Overexpression of Copper/Zinc Superoxide Dismutase in the Median Preoptic Nucleus - John P. Collister; Mitch Bellrichard; Donna Drebes; David Nahey; Jun Tian; Matthew C. Zimmerman (New Horizons in Medicine and Medical Research Vol. 9, 2022)
The brain senses circulating levels of angiotensin II (AngII) through circumventricular organs such as the subfornical organ (SFO), and is hypothesized to regulate sympathetic nervous system output accordingly. The cellular signaling processes involved in these exchanges, however, are still unknown. In this study, we tested the hypothesis that overproduction of intracellular superoxide \((O_2^-)\) , in the median preoptic nucleus (MnPO) is an underlying mechanism in the long-term hypertensive effects of chronic AngII. Adenoviral vectors encoding human CuZnSOD (AdCuZnSOD) or control vector (AdEmpty) were injected directly into the MnPO of rats implanted with aortic telemetric transmitters for recording of arterial pressure. After a three-day saline infusion control phase, rats were given AngII (10 ng/kg/min) intravenously for ten days. Rats over-expressing CuZnSOD (n = 7) in the MnPO had a blood pressure increase of only 6 ± 2 mmHg after ten days of AngII infusion while blood pressure increased 21 ± 4 mmHg in AdEmpty-infected rats (n = 9). These findings back up the theory that \((O_2^-)\) generation in the MnPO plays a role in the development of chronic AngII-dependent hypertension.